Generation of Functional Vascular Endothelial Cells and Pericytes from Keratinocyte Derived Human Induced Pluripotent Stem Cells - Selin Pars; Kevin Achberger; Alexander Kleger; Stefan Liebau; Natalia Pashkovskaia (Cells, 2021)
Human induced pluripotent stem cell (hiPSC)-derived endothelial cells (ECs) and pericytes provide a powerful tool for cardiovascular disease modelling, personalized drug testing, translational medicine, and tissue engineering. Here, we report a novel differentiation protocol that results in the fast and efficient production of ECs and pericytes from keratinocyte-derived hiPSCs. We found that the implementation of a 3D embryoid body (EB) stage significantly improves the differentiation efficiency. Compared with the monolayer-based technique, our protocol yields a distinct EC population with higher levels of EC marker expression such as CD31 and vascular endothelial cadherin (VE-cadherin). Furthermore, the EB-based protocol allows the generation of functional EC and pericyte populations that can promote blood vessel-like structure formation upon co-culturing. Moreover, we demonstrate that the EB-based ECs and pericytes can be successfully used in a microfluidic chip model, forming a stable 3D microvascular network. Overall, the described protocol can be used to efficiently differentiate both ECs and pericytes with distinct and high marker expression from keratinocyte-derived hiPSCs, providing a potent source material for future cardiovascular disease studies.